Can a mobile app improve the quality of patient care provided by trainee doctors? Analysis of trainees' case reports. Issue 9 (21st September 2016) - Webb, Katie; Bullock, Alison; Dimond, Rebecca; Stacey, Mark
Abstract : Objectives: To explore how a medical textbook app ('iDoc') supports newly qualified doctors in providing high-quality patient care. Design: The iDoc project, funded by the Wales Deanery, provides new doctors with an app which gives access to key medical textbooks. Participants' submitted case reports describing self-reported accounts of specific instances of app use. The size of the data set enabled analysis of a subsample of 'complex' case reports. Of the 568 case reports submitted by Foundation Year 1s (F1s)/Year 2s (F2s), 142 (25%) detailed instances of diagnostic decision-making and were identified as 'complex'. We analysed these data against the Quality Improvement (QI) Framework using thematic content analysis. Setting: Clinical settings across Wales, UK. Participants: Newly qualified doctors (2012–2014; n=114), F1 and F2. Interventions: The iDoc app, powered by Dr Companion software, provided newly qualified doctors in Wales with a selection of key medical textbooks via individuals' personal smartphone. Results: Doctors' use of the iDoc app supported 5 of the 6 QI elements: efficiency, timeliness, effectiveness, safety and patient-centredness. None of the case reports were coded to the equity element. Efficiency was the element which attracted the highest number of case report references. We propose that the QI Framework should be expanding to include 'learning' as a 7th element. Conclusions: Access to key medical textbooks via an app provides trusted and valuable support to newly qualified doctors during a period of transition. On the basis of these doctors' self-reported accounts, our evidence indicates that the use of the app enhances efficiency, effectiveness and timeliness of patient-care in addition consolidating a safe, patient-centred approach. We propose that there is scope to extend the QI Framework by incorporating 'learning' as a 7th element in recognition of the relationship between providing high-quality care through educational engagement.